High-resolution sequence stratigraphy of the Arab-D Reservoir, Khurais Field, Saudi Arabia - Al-Awwad, Saad Fahd (Curtin University, 2013)
The subject of analysis in this study is the world’s most abundant oil reservoir, the Arab-D reservoir in the world’s second largest onshore oil field, Khurais Field. The study conducted high-resolution lithofacies analysis (10 cm-scaled) of the Arab-D reservoir from 32 cored wells in Khurais Field to construct a high-resolution depositional cyclicity model that deciphers the architectural distribution of the reservoir’s lithofacies and allows the mapping of the reservoir’s porosity-permeability distribution.